Subcutaneous Ocrelizumab in Patients With Multiple Sclerosis: Results of the Phase 3 OCARINA II Study - Newsome, Scott D; Krzystanek, Ewa; Selmaj, Krzysztof W; Dufek, Michal; Goldstick, Lawrence; Pozzilli, Carlo; Figueiredo, Catarina; Townsend, Ben; Kletzl, Heidemarie; Bortolami, Oscar; Zecevic, Dusanka; Giacobino, Caroline; et al. (Neurology, 2025)
BACKGROUND AND OBJECTIVES: IV-administered ocrelizumab (OCR) is approved for the treatment of relapsing and primary progressive multiple sclerosis (RMS/PPMS). OCARINA II (NCT05232825) was designed to demonstrate noninferiority in drug exposure of OCR subcutaneous (SC) vs IV administration. METHODS: This phase 3, randomized, open-label study enrolled OCR-naive patients aged 18-65 years with RMS/PPMS and an Expanded Disability Status Scale score of 0-6.5. Patients received OCR IV 600 mg or OCR SC 920 mg (controlled period), followed by OCR SC 920 mg every 24 weeks, up to week 96 (OCR IV/SC and OCR SC/SC). The primary end point was OCR area under the serum concentration-time curve from day 1 to week 12 (AUCW1‒12); other end points included clinical, biomarker, and pharmacodynamic outcomes and safety data. RESULTS: Baseline demographics were balanced across OCR IV/SC and OCR SC/SC arms (N = 118/118, 40.0 ± 11.9/39.9 ± 11.4 years, 59.3%/65.3% female, 89.0%/89.0% with RMS). The study demonstrated noninferiority of OCR SC 920 mg to OCR IV 600 mg for the primary end point AUCW1-12 and also over the dosing interval for AUCW1‒24 (geometric mean ratios [90% CI] 1.29 [1.23-1.35] and 1.27 [1.21-1.34], respectively). At week 48, 111 of 118 (OCR IV/SC) and 114 of 118 (OCR SC/SC) had received OCR SC. A near-complete suppression of MRI activity was reported in OCR IV/SC and OCR SC/SC: 0 of 113 and 0 of 113 patients had T1 lesions while 1 of 114 and 1 of 113 had 2 and 1 new/enlarging T2 lesions, respectively. Two patients (1.9%) in each arm had 1 relapse, and 1 patient (0.9%; OCR SC/SC) had 2 relapses. In both arms, rapid and sustained B-cell depletion was observed and serum neurofilament light chain reduction was comparable. Patients receiving at least 1 dose of OCR SC 920 mg in the OCR IV/SC and OCR SC/SC arms reported adverse events (AEs): 75.4% and 86.4%, and serious AEs: 5.9% and 2.5%. The most frequently reported AEs were injection reactions (IRs, 51.5%); local and systemic IRs were experienced by 117 of 233 patients (50.2%) and 27 of 233 patients (11.6%), respectively. All IRs were mild/moderate; intensity and duration decreased with subsequent injections. DISCUSSION: The OCR SC formulation demonstrated noninferiority to OCR IV formulation regarding drug exposure, providing comparable efficacy and safety and an additional treatment option for patients with multiple sclerosis. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that a single SC injection of 920 mg of OCR achieves a noninferior 12-week area under serum concentration-time curve to that of 2 IV infusions of 300-mg OCR administered 2 weeks apart. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier NCT05232825; submitted: January 27, 2022; first patient enrolled: May 3, 2022; available at: clinicaltrials.gov/study/NCT05232825?term=NCT05232825&rank=1.
Keywords: Humans; chronicko-progresivní roztroušená skleróza; lidé středního věku; Multiple Sclerosis; Multiple Sclerosis, Chronic Progressive; Female; Aged; mladý dospělý; dospělí; injekce subkutánní; výsledek terapie; senioři; lidé; humanizované monoklonální protilátky; Injections, Subcutaneous; Adult; imunologické faktory; Antibodies, Monoclonal, Humanized; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; roztroušená skleróza; Male; Middle Aged; Adolescent; Treatment Outcome; Immunologic Factors; Young Adult; mužské pohlaví; mladiství